2018
DOI: 10.1101/317834
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional degradation: a mechanism of NLRP1 inflammasome activation by diverse pathogen enzymes

Abstract: Inflammasomes are multi-protein platforms that initiate innate immunity by recruitment and activation of Caspase-1. The NLRP1B inflammasome is activated upon direct cleavage by the anthrax lethal toxin protease. However, the mechanism by which cleavage results in NLRP1B activation is unknown. Here we find that cleavage results in proteasomemediated degradation of the N-terminal domains of NLRP1B, liberating a C-terminal fragment 5 that is a potent Caspase-1 activator. Proteasome-mediated degradation of NLRP1B … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
108
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(110 citation statements)
references
References 61 publications
(75 reference statements)
2
108
0
Order By: Relevance
“…In contrast, the mouse orthologues of NLRP1 have been better characterised, as it has been shown that Nlrp1b responds to the lethal toxin of Bacillis anthracis (Boyden & Dietrich, ; Moayeri et al, ; Terra et al, ). Recent work has shed light on to the mechanism of Nlrp1b activation by showing that proteolytic cleavage of Nlrp1b results in ubiquitination of the protein (Chui et al, ; Sandstrom et al, ). This ubiquitination targets the protein for proteasomal degradation, through the N‐end rule‐dependent pathway (Chui et al, ; Sandstrom et al, ).…”
Section: A General Overview Of Inflammasomesmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the mouse orthologues of NLRP1 have been better characterised, as it has been shown that Nlrp1b responds to the lethal toxin of Bacillis anthracis (Boyden & Dietrich, ; Moayeri et al, ; Terra et al, ). Recent work has shed light on to the mechanism of Nlrp1b activation by showing that proteolytic cleavage of Nlrp1b results in ubiquitination of the protein (Chui et al, ; Sandstrom et al, ). This ubiquitination targets the protein for proteasomal degradation, through the N‐end rule‐dependent pathway (Chui et al, ; Sandstrom et al, ).…”
Section: A General Overview Of Inflammasomesmentioning
confidence: 99%
“…Recent work has shed light on to the mechanism of Nlrp1b activation by showing that proteolytic cleavage of Nlrp1b results in ubiquitination of the protein (Chui et al, ; Sandstrom et al, ). This ubiquitination targets the protein for proteasomal degradation, through the N‐end rule‐dependent pathway (Chui et al, ; Sandstrom et al, ). As the C‐terminal end of NLRP1 is constitutively clipped and interacts noncovalently with the rest of the protein, the proteasomal degradation of Nlrp1b liberates a CARD‐containing C‐terminal NLRP1 fragment, which can subsequently assemble into an inflammasome (Chui et al, ; Sandstrom et al, ).…”
Section: A General Overview Of Inflammasomesmentioning
confidence: 99%
See 1 more Smart Citation
“…While PYRIN is autoinhibited through interactions with 14‐3‐3 proteins, it can be activated upon the inactivation of cellular RhoA GTPases by various bacterial toxins (Xu et al, ; Masters et al, ). The mouse NLRP1B sensor is also basally autoinhibited through its N‐terminal regions, which can undergo proteasomal degradation, for example in response to anthrax lethal toxin, leading to the release of the CARD‐containing C‐terminal fragment that oligomerises to recruit caspase‐1 and activate the NLRP1 inflammasome (Chui et al, ; Sandstrom et al, ; Xu et al, ). Other than the inhibitors of the serine proteases DPP8/9 (Okondo et al, ; Zhong et al, ), physiological activators of human NLRP1 inflammasome remain to be discovered.…”
Section: Signals For Inflammasome Activationmentioning
confidence: 99%
“…IpaH7.8‐mediated GLMN depletion therefore results in increased inflammasome‐mediated death of macrophages (Suzuki, Suzuki, Mimuro, Mizushima, & Sasakawa, ). IpaH7.8 can also activate murine NLRP1B through ubiquitination and functional degradation of NLRP1B, whereby degradation of the amino‐terminal of NLRP1B releases a carboxyl terminal fragment able to activate caspase‐1 (Neiman‐Zenevich, Stuart, Abdel‐Nour, Girardin, & Mogridge, ; Sandstrom et al, ). Interestingly, IpaH7.8 does not activate human NLRP1 and, therefore, this pathway would not contribute to inflammasome activation during human Shigella infection.…”
Section: Shigella – Inflammasome Interactions Are Cell‐type Specificmentioning
confidence: 99%